Variable wh-words in Turkish - Görgülü, Emrah. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
This study analyzes the syntactic and semantic properties of wh-words in Turkish. Inview of the fact that wh-words in Turkish do not appear only in wh-questions but occur innon-interrogative environments, it is argued that wh-words do not have inherent quantificational force by themselves. The claim is that wh-words in Turkish are syntacticvariables and are bound by the specific operator(s) in the context in which they appear. Inother words, the semantic content of the wh-words is assigned syntactically. It is proposedthat it is the presence of those operators which assign the interpretation of the wh-words as the negative quantifier, the universal quantifier or the interrogative word.With respect to the negative quantifier reading wh-words receive, it is proposed that it isthe presence of the TP-level Gen-(eric) operator which binds the wh-words and assigns theirreading accordingly. On the other hand, the interaction of the Gen-operator and Neg(ative)operator in the structure assigns the universal quantifier reading to the wh-words. It has alsobeen noted that wh-words are always interpreted as the non-interrogative elements in thedomain of the ki particle. The interrogative reading which wh-words are assigned is accountedfor by the existence of the phonologically null [Qu]-operator in the C-domain which binds the wh-words and determines their reading as interrogative. Such morphological processes aspluralization and reduplication are also noted to be processes which give rise to ambiguous ornon-interrogative reading of the wh-words.To conclude, the analysis of the wh-words as non-quantificational elements and the fact that they are assigned different interpretations in different syntactic contexts in Turkish support the claim that they are variables and are dependent for their interpretation on other elements present in the structure.
Keywords: Turkish language -- Grammar.